Evaluation of Postoperative Pain Following Desarda vs. Lichtenstein Mesh Repair in Inguinal Hernia Surgery - Muhammad Waseem Anwar, Abbas Hassnain Kazmi, Khalid Ibrahim Akhtar, Irfan Nabi Khan, Eishah Qanita, Abdul Wali Khan (Pakistan Journal of Medical & Health Sciences, 2023)
Background: Inguinal hernia repair is one of the most frequently performed surgical procedures globally. While the Lichtenstein mesh repair is widely accepted as the gold standard due to its low recurrence rate, it is associated with mesh-related complications and significant postoperative pain. The Desarda technique, a tissue-based repair method that avoids mesh use, has emerged as a promising alternative, potentially reducing postoperative discomfort and complications. Objectives: To evaluate and compare postoperative pain and recovery outcomes following Desarda versus Lichtenstein mesh repair in patients undergoing inguinal hernia surgery. Study Design & Setting: This comparative study was conducted at Department of General Surgery Fatima Hospital/ABU Amara Medical College Lahore. Methodology: This study enrolled 120 patients diagnosed with unilateral inguinal hernia. Patients were randomly assigned to either Desarda or Lichtenstein repair groups. Patients aged 18 to 60 years with primary inguinal hernia were included. Postoperative pain was assessed using the Visual Analog Scale (VAS) at 6, 12, 24, and 48 hours. Additional analgesic requirements, operative time, hospital stay, and pain-free mobilization time were recorded and analyzed. Results: The Desarda group demonstrated significantly lower mean pain scores at all time intervals compared to the Lichtenstein group (p < 0.001). Operative time and hospital stay were shorter in the Desarda group (p < 0.01). A greater proportion of Desarda patients required no additional analgesia (63.3% vs. 35.0%; p = 0.002) and achieved pain-free mobilization earlier (p = 0.004). Practical Implication: The Desarda technique offers a viable mesh-free option for inguinal hernia repair, associated with reduced postoperative pain and faster recovery, which may improve patient satisfaction and reduce healthcare costs. Conclusion: Desarda repair is an effective alternative to Lichtenstein mesh repair, providing superior postoperative pain control and quicker mobilization. Keywords: Desarda repair, inguinal hernia, Lichtenstein repair, postoperative pain, tissue-based repair